2022
DOI: 10.1186/s13020-022-00568-w
|View full text |Cite
|
Sign up to set email alerts
|

Bioactivities and mechanisms of natural medicines in the management of pulmonary arterial hypertension

Abstract: Pulmonary arterial hypertension (PAH) is a progressive and rare disease without obvious clinical symptoms that shares characteristics with pulmonary vascular remodeling. Right heart failure in the terminal phase of PAH seriously threatens the lives of patients. This review attempts to comprehensively outline the current state of knowledge on PAH its pathology, pathogenesis, natural medicines therapy, mechanisms and clinical studies to provide potential treatment strategies. Although PAH and pulmonary hypertens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 155 publications
1
1
0
Order By: Relevance
“…Resveratrol also inhibited the expression of HIF 1A by suppressing the intracellular signaling pathways MAP/ERK1 and P13K. The suppression of VEGF, a downstream gene of HIF 1A, verified those results 25,40,41 .…”
Section: Novel Treatment: Resveratrolsupporting
confidence: 73%
“…Resveratrol also inhibited the expression of HIF 1A by suppressing the intracellular signaling pathways MAP/ERK1 and P13K. The suppression of VEGF, a downstream gene of HIF 1A, verified those results 25,40,41 .…”
Section: Novel Treatment: Resveratrolsupporting
confidence: 73%
“…In recent years, several studies have shown that natural products can simultaneously intervene in multiple parts of the disease because of multitargets and multipathways. They have significant advantages in the treatment of complex diseases such as PH [ 28 ]. Therefore, in the present review, we reviewed the most popular natural products for treating PH and classified the mechanisms involved in these natural products.…”
Section: Pathological Mechanisms Of Phmentioning
confidence: 99%